2016
DOI: 10.3390/nu8020075
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Intake and Status in 6-Year-Old Icelandic Children Followed up from Infancy

Abstract: High serum 25-hydroxyvitamin D (25(OH)D) levels have been observed in infants in Nordic countries, likely due to vitamin D supplement use. Internationally, little is known about tracking vitamin D status from infancy to childhood. Following up 1-year-old infants in our national longitudinal cohort, our aims were to study vitamin D intake and status in healthy 6-year-old Icelandic children (n = 139) and to track vitamin D status from one year of age. At six years, the mean 25(OH)D level was 56.5 nmol/L (SD 17.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 48 publications
3
20
0
2
Order By: Relevance
“…In line with this, others have previously reported that ethnicity is a significant determinant of s-25(OH)D in children (7,15,20,42) . In addition, we cannot rule out the effect of a potential tracking of vitamin D status from infancy as has been reported previously among 6-year-old Icelandic children (41) . Lastly, genetic factors have also been suggested to regulate vitamin D status (43) and we cannot know if this modified the response to sun exposure, for instance.…”
Section: Discussionmentioning
confidence: 80%
“…In line with this, others have previously reported that ethnicity is a significant determinant of s-25(OH)D in children (7,15,20,42) . In addition, we cannot rule out the effect of a potential tracking of vitamin D status from infancy as has been reported previously among 6-year-old Icelandic children (41) . Lastly, genetic factors have also been suggested to regulate vitamin D status (43) and we cannot know if this modified the response to sun exposure, for instance.…”
Section: Discussionmentioning
confidence: 80%
“…This may have been due to the crudity of our measurement of sunlight exposure, as we measured only outdoor playtime but did not consider the area of skin exposed, sunscreen use or time of day when the exposure occurred, since very little if any vitamin D is produced before 10.00 hours and after 15.00 hours (13) . Several recent studies showed that vitamin D levels could also vary according to social and environmental factors such as skin colour and socio-economic status (45,47,(52)(53)(54) . In our study, we found the risk of vitamin D insufficiency to vary according to parental characteristics (children with the highest risk, that is, children whose mothers reported their own education status but omitted the father's, were likely to be single mothers).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no correlation was observed between age of infants and their respective serum concentrations of 25(OH)D. Carpenter and cols [ 8 ] and Alonso and cols [ 35 ] found an inverse correlation between age and 25(OH)D serum concentrations in American and Spanish infants, respectively. In some studies [ 8 , 58 , 62 , 63 ] conducted with infants and children, researchers found that 25(OH)D serum concentrations decreased with age, with a higher proportion of deficient values found in children over two years of age.…”
Section: Discussionmentioning
confidence: 99%